2020
DOI: 10.1371/journal.pone.0239927
|View full text |Cite
|
Sign up to set email alerts
|

Impact of knowledge and attitude on the utilization rate of cervical cancer screening tests among Ethiopian women: A systematic review and meta-analysis

Abstract: Introduction Cervical cancer is a major public health problem, particularly in resource-limited settings. The use of vaccination and screening tests has reduced the burden of cervical cancer in developed countries. However, the situation is quite the reverse in developing countries, including Ethiopia. Hence, this study aimed to estimate the pooled impact of knowledge and attitude on the prevalence of cervical cancer screening service utilization rates among Ethiopian women. Methods Studies that examined cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 70 publications
(90 reference statements)
1
20
0
Order By: Relevance
“…The pooled odds of knowledge score were 1.61 times greater for women who screened of cervical cancer than for those who do not conduct screening test. Similarly, with systematic review and meta-analysis among Ethiopian women with a favorable knowledge toward cervical cancer screening were 3.2 times more likely to have a test than those with a poor knowledge (Kassie et al, 2020). However, several studies conducted in various parts of Indonesia have revealed that the majority of women do not only have poor knowledge about cervical cancer screening tests, but also have lack of awareness about the illness itself (Endarti et al, 2018;Jaspers et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The pooled odds of knowledge score were 1.61 times greater for women who screened of cervical cancer than for those who do not conduct screening test. Similarly, with systematic review and meta-analysis among Ethiopian women with a favorable knowledge toward cervical cancer screening were 3.2 times more likely to have a test than those with a poor knowledge (Kassie et al, 2020). However, several studies conducted in various parts of Indonesia have revealed that the majority of women do not only have poor knowledge about cervical cancer screening tests, but also have lack of awareness about the illness itself (Endarti et al, 2018;Jaspers et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…More than half of the participants in our study also reported that they were unaware of cervical cancer at all. Previous studies also stated that most Ethiopian women had poor knowledge about cervical cancer [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Persistent infection with oncogenic or high-risk Human papillomaviruses (HR-HPV; e.g., HPV16, 18,31,33,35,39,45,51,52,56,58,59 and 68) is the main cause of cervical cancer [8]. However, a recent study revealed that nearly 5% of cervical cancer cases were not HPV-associated, which is a unique biological entity with a different molecular profile when compared with HPV-associated cancers [2].…”
Section: Introductionmentioning
confidence: 99%
“…Our results regarding BC and CC screening behaviours align with findings from other studies. A meta-analysis conducted by Kassie et al (2020) estimated that the uptake of CCS among women in Ethiopia was 8% and knowledge of CC was significantly associated with the utilisation of CCS. A review of the uptake of BC screening in low-resource countries found that utilisation of BC screening in Asian countries was 19% (Mahumud et al 2020).…”
Section: Discussionmentioning
confidence: 99%